119k views
5 votes
3p - 2(p-4) = 7p + 6

User Thetont
by
5.6k points

1 Answer

2 votes

For this case we must find the value of the variable "p" of the following equation:


3p-2 (p-4) = 7p + 6

We apply distributive property on the left side of the equation taking into account that
+*-=- and
- * - = +:


3p-2p + 8 = 7p + 6

We add similar terms:


p + 8 = 7p + 6

We subtract
7p from both sides of the equation:


p-7p + 8 = 6\\-6p + 8 = 6

We subtract 8 from both sides of the equation:


-6p = 6-8\\-6p = -2

We divide by -6 on both sides of the equation:


p = \frac {-2} {- 6}\\p = \frac {1} {3}

Answer:


p = \frac {1} {3}

User Dsign
by
6.0k points